PENGELOLAAN KETERTIBAN PASAR CURUG KABUPATEN TANGERANG OLEH PERUMDA PASAR NIAGA KERTA RAHARJA - Muhammad Iqbal Rohim; Doddy Mulyono; Guntur Syahputra Saragih (Gapenas Publisher, 2023)
The purpose of this research is to determine the orderly management of the Curug Market, Tangerang Perumda Regency by the Kerta Raharja Commercial Market. Therefore, the focus of this research is the Order Management of the Curug Market, Tangerang Perumda Regency by the Kerta Raharja Commercial Market. The method used in this research is a qualitative approach. This research uses strategic management theory, including environmental observation, strategy formulation, strategy implementation, as well as evaluation and control, including looking at opportunities, strengths, and reducing weaknesses in the Perumda Pasar Niaga Kerta Raharja environment. The data collection techniques used were interviews, observation and documentation studies. The data analysis technique uses analysis techniques according to Miles and Huberman. Meanwhile, to test the validity of the data using triangulation and member checks. The research results show that Perumda Pasar Niaga Kerta Raharja Pasar Curug in managing market order is still not optimal. This is because it is hampered by employee discipline and lack of participation by traders. Lack of education among employees is an inhibiting factor in the process of socializing traders and providing infrastructure to support work programs. To improve optimization. Perumda Pasar Niaga Kerta Raharja Pasar Curug needs to take steps to improve the quality and quantity of human resources and other supporting resources